Oesophageal Cancer Studies in the Caspian Littoral of Iran: The Caspian Cancer Registry - Mahboubi, E. (Nature Publishing Group, 1973)
The results of the first 3 years of cancer registration on the Caspian Littoral are described. The main finding, confirming previous reports, is a very large variation within the region of the incidence of oesophageal cancer. Possible sources of bias are considered and shown to contribute little to the pattern of incidence. Among women there is a thirty-fold variation in the incidence across the regions; among men a ten-fold variation. In the north-east of the region the tumour is at least as common in women as in men, and is more common than almost any tumour anywhere in the world. Among other tumours, stomach cancer has a strikingly uniform incidence by comparison; breast cancer shows an incidence gradient of opposite slope.